Initial Experience with Robotic Retropubic Urethropexy Compared to Open Retropubic Urethropexy. (8th September 2013) - Patel, Pooja R.; Borahay, Mostafa A.; Puentes, Audrey R.; Rodriguez, Ana M.; Delaisse, Jessica; Kilic, Gokhan S.
Abstract : Study Objective . To compare the clinical outcomes of robotic retropubic urethropexy versus open retropubic urethropexy. Design . Retrospective case-control study (II-2). Setting . University Hospital. Patients . All patients who underwent robotic retropubic urethropexy from 1/1/12 to 6/1/12 by a single gynecologic surgeon were included in the case series. The control cases consisted of the last five consecutive open retropubic urethropexies performed by the same surgeon. Main Results . A total of 10 patients (5 robotic cases and 5 open cases) were included in this study. Both groups were similar with respect to age, BMI, and obstetrical history. Mean hospital stay length and mean EBL were overall less for robotic cases than for open cases (1.2 days versus 2.6 days; 169 mL versus 300 mL). One of the 5 patients who underwent the open approach and 2 of the 5 patients who underwent the robotic approach sustained a minor intraoperative complication. All but one patient from each group experienced resolution of incontinence after the procedure. Two of the patients who underwent the open approach had postoperative complications. Conclusions . Robotic retropubic urethropexy may be a feasible alternative to open retropubic urethropexy. A larger study is necessary to support our observations.